POSTMORTEM HEART DISSECTION FOR SUDDEN DEATH EXAMINATION - Al-Turki, Ali Ali; Siamionau, Viachaslau V.; Tsiatsiuyeu, Andrei M. (Universal Journal of Pharmaceutical Research, 2024)
The article describes the postmortem heart examination technique during a forensic autopsy of adults. The heart examination technique is based on the recommendations of scientific societies of pathologists, publications on autopsy techniques used in recent decades. The achievements of morphologists of the second half of the 20th century are also taken into account. The postmortem heart examination technique provides an examination of the coronary vessels, as well as myocardium and heart valves. The possibilities for examination of the elements of the conductive system are also represented. The following method ensures preservation of topographic relationships of morphological structures within the heart and possibility of its re-examination. The postmortem heart examination includes the following stages: examination of the coronary arteries, the making of three transverse incisions from the apex to the middle of the ventricles, “blood flow” incisions taking into account the localization of the main nodes of the conducting system, as well as the peculiarities of the examination of the heart valves. Peer Review History: Received: 1 October 2023; Revised: 6 November; Accepted: 23 December; Available online: 15 January 2024 Academic Editor: Dr. Nuray Arı , Ankara University, Turkiye, ari@ankara.edu.tr Reviewers: Prof. Hassan A.H. Al-Shamahy, Sana'a University, Yemen, shmahe@yemen.net.ye Dr. Rima Benatoui, Applied Neuroendocrinology Laboratory, Faculty of Sciences, University of Annaba, Algeria. benattouiryma@gmail.com Dr. Bilge Ahsen KARA, Ankara Gazi Mustafa Kemal Hospital, Turkey, ahsndkyc@gmail.com